How Does the Digitalization Strategy Affect Bank Efficiency in Industry 4.0? A Bibliometric Analysis - Claudia Gherțescu; Alina Georgiana Manta; Roxana Maria Bădîrcea; Liviu Florin Manta (Systems)
This study conducts a detailed bibliometric analysis of the concept of bank efficiency, investigating its evolution in the scientific literature between 2000 and 2024 in the context of the digital transformation specific to the Industry 4.0 era. Using recognized databases, such as Web of Science and Scopus, the research explores the main trends and themes in the field, as well as the impact of emerging technologies on bank efficiency. Eight major thematic clusters are identified, including “risk”, “‘performance”, “efficiency”, “competition”, “corporate governance” and “banking”, highlighting key dimensions of recent research. The co-citation analysis highlighted central authors like Berger, Sufian, and Casu, along with distinct thematic and regional clusters, underscoring the diversity of research directions in banking efficiency. The co-citation analysis shows the influence of leading institutions and authors, including “University Putra Malaysia”, “World Bank”, and “NBER, United States”, which have contributed significantly to the development of the literature. The results indicate that bank efficiency research is dynamic, multifunctional, and ever-expanding, providing an important foundation for future studies that will explore the challenges and opportunities for banks in the era of digitalization and sustainable development.